Effect of Aqueous and Alcoholic Extract of Hydrastiscanadensis Plant on Bacteria Isolated from Otitis Media (Indian Journal of Forensic Medicine & Toxicology, 2021)
The results of the current study showed that the effect of the alcoholic extract of theHydrastiscanadensisplant was more effective than the aqueous extract on the bacteria isolated from otitis media at the sameconcentrations.As the alcoholic extract had the highest effect on proteusmirabilis,Staphylococcusaerues,Staphylococcus epidermidis,Escherichia coli, Pseudomonas aeruginosa and Klepsiella pneumoniawith aninhibition diameter ranging (20, 18, 17, 16 ,16, 15) mm respectively at a concentration of 200 mg/ml,The study also showed that the higher the concentration of the extract, the greater the inhibitory activityagainst the bacterial species,with significant differences in the probability level 0.05 of the two extractson the bacterial species, exceptPseudomonas aeruginosa, Staphylococcusaerues there was no significantdifference in the effect.